Effect of Media and Plant Growth Regulator on Proliferation of Somatic Embryogenic Callus of Oil Palm (Elaeis gueenesis Jacq.) - Sulaksono, Gogoh; Hasmeda, Mery; Hanum, Laila; Wendra, Fahmi; Santika, Baitha (AGRIVITA Journal of Agricultural Science, 2024)
The Pisifera type oil palm is an important palm variety and mostly used as a pollen source to produce Tenera commercial hybrid varieties. This research on proliferating fertile Pisifera oil palm callus using somatic embryogenesis method was conducted at the Tissue Culture Laboratory of PT. Sampoerna Agro, Tbk from February to August 2021 to find out the optimum basal media and the concentration of growth regulators on callus proliferation. The planting material was the primary callus from the previous research. This study used a factorial Completely Randomized Design with two factors. The first factor involved two types of basal media: MS and Y3, and the second factor consisted of different concentrations of growth regulators (PGR). All treatments were repeated three times. The results showed that the use of MS media supplemented with 6 mg/l NAA and 0.5 mg/l 2,4-D was the most effective treatment for the proliferation of embryogenic callus in term of callus initiation time, the capacity of primary callus formation, primary calli morphology and proliferation, and callus fresh weight.